Virtual Learning Environments from localization point of view - Dagienė, Valentina; Jevsikova, Tatjana (Lietuvos matematikos rinkinys, 2005)
For better learning achievements in a networked society the great variety of virtual learning environments (VLE) is being developed and used. VLE is going to be integrated into Lithuanian education. One of the steps during the integration is VLE localization into Lithuanian.In this paper the main aspects of VLE localization are presented. Since most of modern VLEs are webbased, their localization is based not only on common software localization principles, but also onsweb site localization specifics. Two open source VLEs –  ``  `  ATutor“ and  `` ` Moodle“ – are analyzed. Basic locale items (as characters encoding, date and time formats, calendar format, parameters in localization strings, etc.) used in VLE, are discussed, their adaptation to Lithuanian locale is evaluated. Additional requirements for VLE localization are presented.As a result of the analysis, not sufficient VLE internationalization level has been noticed. Some locale items, used in VLE, are not compatible with Lithuanian locale. To solve these problems, VLE source should be modified, thus open source VLEs have an advantage from localization point of view.
Keywords: virtual learning environment; e-learning; localization; internationalization; locale